Exposure to biological and chemical agents at biomass power plants. (October 2016) - Laitinen, Sirpa; Laitinen, Juha; Fagernäs, Leena; Korpijärvi, Kirsi; Korpinen, Leena; Ojanen, Kari; Aatamila, Marjaleena; Jumpponen, Mika; Koponen, Hanna; Jokiniemi, Jorma
Abstract: The increasing use and production of bioenergy means that the number of employees working in this area will inevitably grow, making it ever more important to know the health and safety issues involved in the biomass supply chain. Our aim was to determine the exposure of employees to biological and chemical agents during various work tasks at different biomass-fuelled power plants in Finland. The study included technical surveys on biomass operations and occupational measurements at three CHP plants. Workers' main health risks were bacteria and fungi, which were easily spread to the air during heavy biomass processes. The exposure levels of actinobacteria, bacterial endotoxins and fungi were high, especially during the unloading of peat and wood chips. In addition, workers were exposed to mechanical irritation caused by organic dust, and chemical irritation caused by volatile organic compounds and components of diesel exhausts. Multiple exposures to these agents may simultaneously have synergistic health effects on workers' lower and upper respiratory tracts. During operations, workers were also exposed to endotoxins, actinobacteria and fungi, especially during the cleaning and handling of wood chips in silos and while working near screens or crushers. The measured concentrations exceeded the limit values proposed for these agents. The highest concentration of volatile organic compounds was found near conveyors. On the basis of these measurements, we suggested best practices for the power plants. The levels of biological agents in outdoor measurements reflected only low spreading of contaminants from power plants to the environment. Highlights: Unloading, screening and crushing are the most hazardous stages in the processing of indigenous biofuels. The main occupational hazard is organic dust including actinobacteria, bacterial endotoxins and fungi. Workers exposure to volatile organic compounds and diesel exhausts simultaneously with biological agents.